PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT JET TEKNOLOGI EKSPRESS CABANG CISAUK-TANGERANG - Riyanto, Teguh; Boro Tura, Theobaldus (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the influence of the work environment and compensation on employee performance at PT. Jet Teknologi Express Cisauk – Tangerang Branch both partially and simultaneously. The method used is quantitative. The sampling technique used saturated samples and the sample obtained in this study amounted to 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, coefficient analysis, determination coefficient analysis and hypothesis tests. The results of this study show that the work environment (X1) has a significant effect on employee performance (Y) with the regression equation Y=5+0.547X1+e, the hypothesis test is obtained from the t-value calculated > the t-table, which is (7.824>2.01174). There is also a significant influence between compensation (X2) on employee performance (Y) with the regression equation Y=5+0.180X2+e, the hypothesis test obtained a t-value calculated > t table which is (4,757>2.01174) and there is a positive and significant influence between the work environment (X1) and compensation (X2) together on the performance of employees (Y) at PT. Jet and technology of the Cisauk – Tangerang Branch Express with the equation Y=5+0.547X1+0.180X2+e, the value of determination or contribution of influence is 0.570 or 57% and the remaining 43% is influenced by other factors. The hypothesis test obtained a value of f calculated > f table, namely (31,183>3.19). This shows that there is an influence between the work environment and compensation on the performance of employees of PT. Jet Teknologi Express Cisauk Branch – Tangerang.